Family Instructions for the Yan Clan and Other Works by Yan Zhitui (531-590s) - Zhitui, Yan (Library of Chinese Humanities, 2021)
This is a new, accurate translation into English, with critical introduction and notes and based on recent scholarship, of Yan Zhitui's (531-590s) complete literary works, including his famous Family Instructions, his self-annotated poetic autobiography, a never-before-translated fragmented rhapsody questioning the phenomena of the natural world, and his extant poems. The appendix provides a translation of Yan's biographies in dynastic histories.